Effectiveness of the Direct Instruction Model in the Merdeka Curriculum on Basic Pencak Silat Technique Skills at SMPN 1 Majalaya - Rahma, Fika Aulia; Dimyati, Akhmad; Susanti, Evi (Journal of Educational Sciences, 2023)
Education is a means or bridge for humans to be able to develop their potential through the learning process they have obtained. The implementation of physical education learning will be ineffective, because the learning model chosen by the teacher is inaccurate, because the learning model will influence student learning outcomes, so it is necessary to use a learning model that can be applied and adjusted based on the characteristics of the learning material. The aim of this research is to find out about the effectiveness of the direct instruction learning model on the basic pencak silat technical abilities of grade 7 students at SMPN 1 Majalaya. The method used in this writing is an experiment with a One-Group Pretest-Posttest design. Based on the results of the Wilcoxon test table, the Sig value is known. (two tilled) of 0.000 < 0.05, then the hypothesis is accepted. So it can be concluded that there is a difference between the pretest and posttest which means that the use of the direct instruction model is effective in basic techniques in learning pencak silat at SMPN 1 Majalaya. This is also supported by the average N-gain percent value of 60% which is in the table. The criteria indicate a fairly effective level.